(untitled) (American Journal of Islam and Society, 2012)
Ather Farouqi’s edited book Muslims and Media Images: News Versus Views examines the Hindi and Urdu press as well as Hindi and regional language films. The uniqueness of the collection lies in the grounded approach taken to study the topic of media images of Indian Muslims. Along with an introduction and two appendices, this volume consists of nineteen mainly short chapters organized in four sections that highlight the experiences of media practitioners, who provide their own accounts and testimonies. Consisting of journalists, newspaper editors, filmmakers, and academics ‒ the contributors to this volume are writing from the field, while incorporating historical components in a tone embedded in a storytelling style. Although certain generalizations and scattered links between chapters might distract readers, such grounded conversations are valuable to academics interested in generating theory from the practice of making media. Most authors provided vivid examples here from their own involvement in the process of writing or editing news, while relying on a minimal use of citations, which presents an interesting alternative format to standard academic studies. This book offers relevant reading to scholars of Islamic studies, communication, journalism, cinema, political science, and readers interested in Indian media and Muslim representations ...